Numerical simulation and prototype experiment of integrated electrohydraulic pump. (July 2022) - Fei, Sun; Hong, Ji; Yanbo, Peng; Chen, Li
Integrated electrohydraulic pump (IEHP) is conceived as an innovative design concept to achieve the higher power density, lower noise level, and leakage-free with respect to the traditional hydraulic power units. Nevertheless, the complex cooling circuit may increase the flow resistance, reducing the effective delivery flow rate of IEHP, which will be more serious at high rotational speed. In this context, a novel centrifugal charging pump (CCP) integrated on the hollow drive shaft is arranged on the suction path of positive-displacement vane pump (main pump) to boost its inlet pressure, thus efficiently improving the suction capability of IEHP. The contribution of this study is to develop a full flow field CFD model of IEHP, in which the fluid domain of main pump and CCP are connected in series. Based on the CFD model validated subsequently by prototype experiment in terms of volumetric efficiency, the charging effect of CCP modeled with different geometric parameters, at 1, 500 r/min, has been investigated. Finally, combined with experiment and simulation, the delivery flow rate of IEHP, in the speed range 600–6, 000 r/min, are also analyzed by means of comparing with a standard vane pump. The results show that the CCP makes an outstanding contribution to the filling of main pump, especially when the rotational speed exceeds 3, 000 r/min; Since then, the flow rate saturation of standard vane pump tends to occur due to serious incomplete filling, while the IEHP still maintains valid output. It can be concluded that, with the help of charging effect of CCP, the IEHP can keep the same volume efficiency as the vane pump under rated speed, and there is a certain potential for the application of IEHP in a wide speed range.